2013
DOI: 10.1007/s00405-013-2604-z
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma antigen as a marker of sinonasal inverted papilloma

Abstract: This prospective study aimed to evaluate the usefulness of squamous cell carcinoma antigen (SCCA) as a clinical marker of sinonasal inverted papilloma (IP). The potential benefit of SCCA in the diagnosis of unilateral nasal pathology and as a marker of hidden recurrence was evaluated as well. Blood samples from patients with sinonasal IP were examined to determine serum SCCA levels before surgery, the day after surgery, and every 6 months during follow-up. Preoperative and postoperative levels of SCCA were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…In Zweifelsfällen ist eine Kernspintomografie ergänzend sinnvoll. Die Bestimmung des SCC-Antigen (Squamous cell carcinoma antigen) hat sich als sehr guter Verlaufsparameter erwiesen und ist auch bei unklaren Papillom-Rezidiven angezeigt [1031][1032][1033][1034]. Das Verhältnis SCCA2/SCCA1 kann als Hinweis auf ein Karzinom im IP eingesetzt werden [1032].…”
Section: Benigne Tumoren -Invertiertes Papillomunclassified
“…In Zweifelsfällen ist eine Kernspintomografie ergänzend sinnvoll. Die Bestimmung des SCC-Antigen (Squamous cell carcinoma antigen) hat sich als sehr guter Verlaufsparameter erwiesen und ist auch bei unklaren Papillom-Rezidiven angezeigt [1031][1032][1033][1034]. Das Verhältnis SCCA2/SCCA1 kann als Hinweis auf ein Karzinom im IP eingesetzt werden [1032].…”
Section: Benigne Tumoren -Invertiertes Papillomunclassified
“…Following Yasumatsu, other authors also found a correlation between SCCa and inverted papilloma disease status . However, these were small studies, and only patients with primary inverted papilloma were included.…”
mentioning
confidence: 99%
“…It has been observed throughout the recent years that patients with IP show elevated SCCA in both IP diagnosed de novo and recurrence. Moreover, SCCA level was reduced in all patients after the surgery and no elevation was observed in sinus inflammatory conditions [ 30 , 31 , 33 ]. In some patients, circulatory SCCA was growing even before it was possible to observe a tumor macroscopically [ 30 ].…”
Section: Recurrence and Malignant Transformation Risk Factorsmentioning
confidence: 99%